Application of experimental design for photodegradation of rose bengal (acid red 94) - Muhamad Zulhelmi, Mohamad Fithol (2009)
Advance Oxidation Process (AOP) of Acid Red 94 (AR 94) by UV and H2O2 system were carried out in this study. AR 94 was irradiated with UV light in the presence of H2O2. The photodegradation process of the dye was monitored spectrophotometrically. Effects of AR 94 and H2O2 concentrations, pH, and irradiation time for photodegradation of AR 94 were investigated throughout this research while other experimental conditions were fixed at specific values. Statistical approach was employed to study the effect of selected parameters with the aid of Design-Expert® 7.1.6 software. Two level factorial design was employed for the experimental design. From the result, it is shown that the highest percent of AR 94 degradation can be achieved was 92.31%. From the analysis of variance, it is found that the AR 94 concentration, pH, and time were significant factors along with the interaction factors of AR 94 concentration, H2O2 concentration, and pH which gave significant effect for AR 94 degradation as well. Then, the optimization process was done using response surface methodology (RSM). Based on ANOVA result, the proposed model can be used to navigate the design space. It was found that the response of AR 94 decolorization is very sensitive to the independent factor of pH. The proposed model for central composite design fitted very well with the experimental data with R2 and R2adj correlation coefficients of 0.976 and 0.943, respectively. Analysis of results data shown that the optimum conditions suggested by the design of experiment were; 20μM AR 94, 0.05 M H2O2, 3.75 pH value and irradiation time 30 minutes.